The Eventualization of Evidences: An Analysis of the Relationships between Sayabilities and Visibilities after Foucault - Renggli, Cornelia (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2007)
Discourse analysis after Michel FOUCAULT has barely yet considered images. This lacuna may be considered amazing, as FOUCAULT himself did analyze images often and devoted himself to the relationship between the visible and the sayable. Therefore, this paper deals with the analysis of the relationships between visibilities and sayabilities. The analysis, which includes pictures as well as texts, starts with the question of how something becomes a problem at a certain place and a certain time. This examination of problematizations applies instruments of FOUCAULTian archeology and genealogy. The procedure is based upon the method of participant observation and consists in an eventualization of evidences: at first, it is necessary to break through evidences in order to examine them afterwards as discursive and visual events along the axes of knowledge, power and ethics. In this way, the observed objects, observations and observing subjects are examined in order to describe the relationships between sayabilities and visibilities. This procedure is presented through an example of how disability is shown in the public.URN: urn:nbn:de:0114-fqs0702239